Countering climate-related security risks in the Sahel: Strengthening climate resilience and peace - Sarzana, Carolina; Pacillo, Grazia; Laderach, Peter; Gadeberg, Marianne (2025)
In the Sahel, community tensions and conflicts are exacerbated by droughts and irregular floods. In response, researchers from the Alliance of Bioversity International and CIAT (the Alliance), contributing to the CGIAR Research Initiative on Climate Resilience (ClimBeR), investigated how climate-change impacts can cause and interact with security threats in Burkina Faso and Mali. They engaged national and regional stakeholders to validate their findings and recommend best-bet solutions. Authorities in both countries are now set to integrate these insights into their first-ever national climate security strategies.